Respuesta :
We have the expression -1(2x + 3) - 2(x - 1).
Distribute the -1 across the 2x and 3.
-1(2x + 3) - 2(x - 1) = -2x - 3 - 2(x - 1)
Now distribute the 2 across the x and -1.
-2x - 3 - 2(x - 1) = -2x - 3 - 2x + 2
Combine like terms.
-2x - 3 - 2x + 2 = -4x - 1
So, D -4x - 1 is the answer.
Distribute the -1 across the 2x and 3.
-1(2x + 3) - 2(x - 1) = -2x - 3 - 2(x - 1)
Now distribute the 2 across the x and -1.
-2x - 3 - 2(x - 1) = -2x - 3 - 2x + 2
Combine like terms.
-2x - 3 - 2x + 2 = -4x - 1
So, D -4x - 1 is the answer.
Answer:
( D) -4x-1
Step-by-step explanation:
-1(2x+3) -2(x-1)
-2x-3-2(x-1)
Answer -4x-1